2021
DOI: 10.48550/arxiv.2106.13174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resource Management for Transmit Power Minimization in UAV-Assisted RIS HetNets Supported by Dual Connectivity

Abstract: This paper proposes a novel approach to improve the performance of a heterogeneous network (HetNet) supported by dual connectivity (DC) by adopting multiple unmanned aerial vehicles (UAVs) as passive relays that carry reconfigurable intelligent surfaces (RISs) . More specifically, RISs are deployed under the UAVs termed as UAVs-RISs that operate over the micro-wave (µW) channel in the sky to sustain a strong line-of-sight (LoS) connection with the ground users. The macro-cell operates over the µW channel based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…In [83], the authors have proposed a multiple UAVs mounted RISs system that communicates in HetNets supported by dual connectivity. The proposed system operated with micro-wave channels at UAVs-RISs while maintaining the LoS communication with the users.…”
Section: E Deep Reinforcement Learning In Uav-rismentioning
confidence: 99%
See 2 more Smart Citations
“…In [83], the authors have proposed a multiple UAVs mounted RISs system that communicates in HetNets supported by dual connectivity. The proposed system operated with micro-wave channels at UAVs-RISs while maintaining the LoS communication with the users.…”
Section: E Deep Reinforcement Learning In Uav-rismentioning
confidence: 99%
“…The Federated learning-based UAV-RIS model could be a possible definite solution towards various problems we talk about such as secrecy performance, energy efficiency, and spectral efficiency. In [80]- [83], the authors have identified that implementation of various DRL techniques has enhanced the energy performance of UAVs and reduced the latency in data transmission. Whereas, few other stand-alone systems work also indicated that implementing federated learning in their proposed system models has shown significant performance gain.…”
Section: B Federated Learning-based Uav-assisted Rismentioning
confidence: 99%
See 1 more Smart Citation